Disinformation and ‘Affect’ in the Cyberspace : The Case of Modi’s ‘New India' - Agrawal, Kshitij; Weinfurter, Jaroslav; Christie, Micah; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis ponders how democracies can stay intact in the digital age, problematizing disinformation today with the 'affective' dimensions of emotions. What emerges is a carefully constructed affective digital architecture, armed with reactionary publics & labelling of adversaries. The qualitative research on disinformation cases & search trends explore positive & negative 'affects' channelled or repressed in the Indian digital space to manufacture 'enemies' & 'others' to promote a populistic agenda. Such forces generate ignorance & affectivity to amplify populistic currents, curtail free expression & harm democracy in the long run.
Vedoucí práce: Jaroslav Weinfurter
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses